ChemInform Abstract: Palladium‐Catalyzed Annulation of Internal Alkynes: Direct Access to π‐Conjugated Ullazines. Issue 44 (13th October 2016) - Wan, Danyang; Li, Xiaoyu; Jiang, Ruyong; Feng, Boya; Lan, Jingbo; Wang, Ruilin; You, Jingsong
Abstract: The Pd‐catalyzed direct C—H cyclization of dibromoarylpyrroles with various diarylalkynes produces the title ullazines in good yields.